Territorialização militar em rede e o imperialismo estadunidense na América Latina: um novo código geopolítico? - Sousa, Rodrigo Pina de (2009)
This work approaches the military presence of US in Latin America, within the scope of geopolitics of the new imperialism. Although the Latin America is not treated like a priority in the context of the global strategy adopted by United States, when analyzed through the prism of militarization, it is an example of a transition of geopolitical conduct, consequence of a change in the geopolitical code. If we analyze the new code that is being applied on Latin America by the US, we can notice a strategy of decentralization and military repositioning. We call this process of military network territorialization, and through this process we are able to understand in which way a military network-territory is defined from the geopolitics of the new imperialism of US in Latin America. Our objective is to comprehend the relations of power captained by the new US imperialism in its conduct with some Latin-American countries, and focusing centrally in the direction of the militarization (especially with the installation and the use of military air bases and airfields). The legality of a new geopolitical code that redefines in expressive pace the strategy of the US imperialism, and orientates the pre-configuration of a military network-territory on Latin American, in which the FOLs (Forward Operating Locations) perform a crucial role is licit. The new geopolitics of imperialism has been consolidated by the marks of the actual geopolitical code of prevention: the territorial disposition anticipated and the preparation. The new code points to the need of a reinterpretation of the territory category, and, for one more contribution of political geography to the reading of a contemporaneous world through the prism of the political-military side of the new imperialism.